THE POTENTIAL OF NATIONAL INCOME ACCOUNTING TECHNIQUES FOR THE EVALUATION OF BUSINESS RESULTS - Sharaf, Dr. Hussein; Sharaf, Dr. Hussein (Dirasat in Economics and Business, 1972)
The following abstracts are short synopses of articles appearing in the Arabic part of the Review. They are summarized here for the benefit of those who cannot read Arabic. In a like manner, each major, English or French article is presented as a short résumé in the Arabic section.